Build Operate Transfer: Does it Apply Universally? The Case of Dinoyo Malang City Mall, Indonesia - Luqman Hakim (Magister Administrasi Publik, 2019)
Politics change, so does public administration. The aim of this research is to evaluate the Build Operate Transfer (BOT) – based policy in the modernization of Dinoyo Traditional Market Malang city, East Java province, Indonesia. The research was conducted during 20172018. The research was based on a qualitative research design, and used in-depth interview, observation and documentation to collect data. Research results showed that the change in Indonesian political landscape that begin with the step down of President Soeharto from office in May 1998, also served as a milestone of radical change in public administration. The change in politics from authoritarianism towards democracy, also affected the way government is organized and the delivery of public services are delivered from an over centralized to a decentralized approach. The BOT scheme in the public service delivery, is a public private partnership arrangement, which is a new alternative available to deliver public services. The Dinoyo Traditional Market, which was developed by the central government in 1980s, has since been redeveloped to become a modern market that is today known as Malang City Mall. Under the BOT scheme, a group of private Indonesian Chinese investors financed the reconstruction of the market, and have the opportunity to operate the mall for a certain period, after which ownership will revert to the city government. Some of the adverse effects of BOT arrangement include decline in income of small traditional traders due to the loss of space to carry out their activities, marginalization of traditional tenants as their products are replaced by domestically manufactured and imported goods, caused disputes due to the feeling of unfairness.